2016
DOI: 10.1186/s12978-016-0175-3
|View full text |Cite
|
Sign up to set email alerts
|

The Antenatal Corticosteroids Trial (ACT)’s explanations for neonatal mortality - a secondary analysis

Abstract: BackgroundThe Antenatal Corticosteroid Trial assessed the feasibility, effectiveness, and safety of a multifaceted intervention to increase the use of antenatal corticosteroids (ACS) in mothers at risk of preterm birth at all levels of care in low and middle-income countries. The intervention effectively increased the use of ACS but was associated with an overall increase in neonatal deaths. We aimed to explore plausible pathways through which this intervention increased neonatal mortality.MethodsWe conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 16 publications
1
17
1
1
Order By: Relevance
“…This may have been due to the administration of corticosteroids to women thought to be at risk for preterm birth who ultimately delivered late preterm or term infants. On secondary analysis of these data, there was no significant increase in risk of PSBI in the intervention clusters who received antenatal corticosteroids when compared to the control clusters [ 31 ]. When the composite outcome of PSBI and death was analyzed, risk was increased in the intervention clusters (RR 1.17, 95 % CI 1.04–1.30), which was driven by the difference among infants with a birth weight greater than or equal to the 25 th percentile.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to the administration of corticosteroids to women thought to be at risk for preterm birth who ultimately delivered late preterm or term infants. On secondary analysis of these data, there was no significant increase in risk of PSBI in the intervention clusters who received antenatal corticosteroids when compared to the control clusters [ 31 ]. When the composite outcome of PSBI and death was analyzed, risk was increased in the intervention clusters (RR 1.17, 95 % CI 1.04–1.30), which was driven by the difference among infants with a birth weight greater than or equal to the 25 th percentile.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter randomized trial in low- and middle-income countries found that ANS not only did not decrease mortality rates for infants who were born with a birthweight <5th percentile but it also increased neonatal mortality rates for all infants who were exposed to ANS prenatally, which could not be attributed to other components of the treatment intervention. 19 , 20 …”
Section: Commentmentioning
confidence: 99%
“…Publizierte Daten zur Anwendung der pränatalen Steroidtherapie in hoch entwickelten Versorgungssystemen stimmen mit Studien, die in Länder mit eingeschränkten Ressourcen und mit niedrigem Einkommen erhoben wurden, nicht überein. In ärmeren Ländern konnte bei der Antenatal Corticosteroids Trial (ACT) eine erhöhte Neugeborenen-Mortalität und eine steigende neonatale und maternale Infektionsrate nachgewiesen werden [31,32]. Auch wenn eine klare Interpretation der adversen Daten nicht möglich erscheint, sollte laut dem Ergebnis der sekundären Analyse die pränatale Kortikosteroidapplikation in Regionen mit wenig Ressourcen in derer Effektivität und Sicherheit weiter untersucht werden [31,32].…”
Section: Wirkungen Beim Frühgeborenenunclassified